Poly[diaqua[μ2-1,4-bis(pyridin-3-ylmethyl)piperazine][μ2-4-(2-carboxylatoethyl)benzoato]cobalt(II)] - Frederick C. Ezenyilimba; Robert L. LaDuca (IUCrData)
A layered cobalt coordination polymer containing both 4-(2-carboxylatoethyl)benzoate (ceb) and 1,4-bis(3-pyridylmethyl)piperazine (3-bpmp) ligands, [Co(C10H8O4)(C16H20N4)(H2O)2]n or [Co(ceb)(3-bpmp)(H2O)2]n, was isolated and structurally characterized by single-crystal X-ray diffraction. Chain-like [Co(ceb)(H2O)2]n units are oriented parallel to [101]. These are connected into (4,4)-grid coordination polymer layers by tethering 3-bpmp ligands. The layer motifs stack in an AAA pattern mediated by O—H...N hydrogen-bonding interactions between the aqua ligands in one layer and 3-bpmp piperazinyl N atoms in the abutting layer.